Using Multivariate Concept-Mapping for Examining Client Understandings of Counselling - Bedi, Robinder P; Alexander, David A (Revue canadienne de counseling et de psychothérapie, 2010)
Counsellors rely on sound research to inform their practice. However, many methods in counselling research that seek to categorize clients’ experiences (including the Critical Incident Technique) inadvertently examine the client’s perspective through the lens of investigator-derived or counsellor-derived constructs and categories – thereby blurring counsellor and client perspectives. Multivariate concept-mapping (MVCM) is a mixed methods research design that ensures the client’s perspective is a more fitting representation of the client’s subjective experience of counselling processes. This article introduces MVCM as an analytical method for understanding the clients’ perspective on counselling and provides a guide for conducting MVCM research on counselling processes. It is hoped that this article will result in greater awareness of this research method amongst counsellor educators and counselling researchers in Canada, resulting in a better understanding of the client’s experiences of counselling processes, which should inevitably benefit counselling practitioners. In the meantime, this article can serve as an impetus for counsellors to carefully scrutinize the categorization-based research on the client’s perspective that they use to inform their practice.